2020
DOI: 10.26832/24566632.2020.0503027
|View full text |Cite
|
Sign up to set email alerts
|

An outlook on metabolic pathway engineering in crop plants

Abstract: To produce the essential secondary metabolites, plants are the major and important target source materials for conducting the high-profile metabolic engineering studies. Metabolic pathway engineering of both microorganism targets and plants target contribute towards important drug discovery. In order to efficiently work out in advanced plant metabolic pathway engineering techniques, a detailed knowledge and expertise is essentially needed regarding the plant cell physiology and the mechanics of plant metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Results obtained from the present study revealed that, the PIC values of the markers were found between 0 to 1, which was similar to previous research finding in mung bean (Chen et al, 2021;Dash et al, 2022;Sahoo et al, 2020a). However, the present investigation on trait-based genetic diversity is almost similar to the earlier findings (Sushmita et al, 2021;Sahoo et al, 2020b; of moderate genetic diversity reported in mung bean for the single trait.…”
Section: Polymorphism Information Content (Pic) Valuessupporting
confidence: 92%
“…Results obtained from the present study revealed that, the PIC values of the markers were found between 0 to 1, which was similar to previous research finding in mung bean (Chen et al, 2021;Dash et al, 2022;Sahoo et al, 2020a). However, the present investigation on trait-based genetic diversity is almost similar to the earlier findings (Sushmita et al, 2021;Sahoo et al, 2020b; of moderate genetic diversity reported in mung bean for the single trait.…”
Section: Polymorphism Information Content (Pic) Valuessupporting
confidence: 92%
“…It is especially devastating in the cool-dry growing season. Although urdbean has a short growth duration, progress in breeding cultivars with Powdery mildew disease resistance has been slow (Sahoo et al, 2020b). A factor limiting breeding progress is selection for powdery mildew disease resistance, which is is confined to the cool-dry season (Chankaew et al, 2013).…”
Section: Introductionmentioning
confidence: 99%